Development and Performance Evaluation of New Sustainable Bio-Based Building Insulation Materials - Balo, Figen (Mdpi, 2026)
In this work, a bio-based thermal insulation composite is developed and processed with epoxidized cottonseed oil (ECSO) as a renewable binder; performance is then assessed at material and building levels by using a natural fiber. Composite insulators were synthesized by mixing clay, fly ash, perlite, and eggshell powder with ECSO at different concentrations (45-55 wt%) and curing temperatures (165-205 degrees C). The density, thermal conductivity, compressive and tensile strengths, wear resistance, and water absorption capacity of the obtained composites were investigated in detail in extensive experimental work. The density and thermal conductivity were much dependent on the ECSO content and the curing temperature, unbeknownst to us; they significantly decreased with the increasing ECSO content and curing temperature, due to better binder-filler interaction and increased porosity. Among all the tested samples, the lowest thermal conductivity and density were observed for ECSO36, which suggested the best insulation performance. To validate its real-world usability, the best composite (ECSO36) was also tested by an IES-VE building energy simulation under the climate of Ankara in terms of annual energy consumption and CO2 emission. The results signify that ECSO36 achieves a similar energy consumption and CO2 emission performance to traditional insulation materials. In summary, the results of this work illustrate that ECSO-based composites have excellent potential to be a green and low-carbon alternative for sustainable building insulation applications.
Keywords: bio-based insulation materials; epoxidized cottonseed oil; sustainable building materials; thermal performance; building energy simulation